El Niño-Southern Oscillation warm phase events and precipitation during spring and summer in the central eastern region of La Pampa province (Semiárida, 2024)
The ENSO phenomenon is a climate variability factor that mainly impacts rainfall on a planetary scale and can be anticipated several months in advance. Numerous studies have found that the warm phase of the phenomenon correlates with positive precipitation anomalies in the Argentine Pampean Region; however, more specific studies are required to analyze the spatial variability of rainfall during each ENSO event within this large region and even considering its intensity. The objective of this work was to analyze the distribution of rainfall during ENSO warm phase (EN) events occurring during spring and summer in the central eastern region of La Pampa (LP) province, where the main crop and forage crops are grown. For this purpose, quarterly pluviometric information from 11 localities over a 50-year period was analyzed. In the case of summer, during intense EN events, the range of positive precipitation anomalies ranged from 20 to 66% and, in all localities, the accumulated precipitation exceeded the historical average. During mild to moderate EN episodes, there were no significant differences (p < 0,05) in rainfall with respect to historical averages. In the spring EN episodes, no significant differences (p < 0,05) in rainfall were found with respect to historical averages. From the spatial distribution of rainfall anomalies, certain zonal patterns could be observed. Positive differences during intense summer EN events represent on average about 100 mm in the summer quarter, an additional difference that is considerable for agricultural activities in the study region. In the case of the distribution of rainfall anomalies for spring EN events, a spatial distribution of positive precipitation values was observed sectored in the SE of the province during mild to moderate events, while during intense events the sectored areas with positive values were scattered throughout the study area. This difference in rainfall behavior during EN events according to the season of occurrence represents an important aspect that should be further studied in future investigations.
Keywords: ENSO; precipitation; agricultural planning; pampas steppe